2014
DOI: 10.1063/1.4871362
|View full text |Cite
|
Sign up to set email alerts
|

Design and performance of AERHA, a high acceptance high resolution soft x-ray spectrometer

Abstract: A soft x-ray spectrometer based on the use of an elliptical focusing mirror and a plane varied line spacing grating is described. It achieves both high resolution and high overall efficiency while remaining relatively compact. The instrument is dedicated to resonant inelastic x-ray scattering studies. We set out how this optical arrangement was judged best able to guarantee performance for the 50 - 1000 eV range within achievable fabrication targets. The AERHA (adjustable energy resolution high acceptance) spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 23 publications
(19 reference statements)
0
35
0
Order By: Relevance
“…The line shapes resolved from SrCuO 2 illustrate the need for adequate resolution to observe how simple atomic excitations decompose into more complex and delocalized many-body states, and are broad enough to also be well resolved at recently developed soft X-ray RIXS spectrometers that achieve ∼100 meV resolution [46][47][48][49]. Our earlier EUV studies have shown that orbital excitations inside the insulating gap of CoO and NiO have significantly sharper line shapes that are sensitive to thermal fluctuations [7], with a δE ∼ 70 meV leading edge contour identified at low temperature for the 1 eV excitation in CoO.…”
Section: A New Regime Of Energy Resolutionmentioning
confidence: 99%
“…The line shapes resolved from SrCuO 2 illustrate the need for adequate resolution to observe how simple atomic excitations decompose into more complex and delocalized many-body states, and are broad enough to also be well resolved at recently developed soft X-ray RIXS spectrometers that achieve ∼100 meV resolution [46][47][48][49]. Our earlier EUV studies have shown that orbital excitations inside the insulating gap of CoO and NiO have significantly sharper line shapes that are sensitive to thermal fluctuations [7], with a δE ∼ 70 meV leading edge contour identified at low temperature for the 1 eV excitation in CoO.…”
Section: A New Regime Of Energy Resolutionmentioning
confidence: 99%
“…Light elements, however, are the building blocks of all compounds relevant in biology and life research. Additionally, the detection efficiency of soft X-ray spectrometers is also low due to grazing incidence gratings and long distances between source and optical element, which lead to a very small solid angle [13][14][15]. This results in a need for brilliant light sources.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the experimental requirements, some reach theoretically high resolution up to E/ΔE = 10 5 . However, these are very large instruments with up to 15 m arm length [14,19,20,[22][23][24][25][26]. Other spectrometer designs use additional optical elements to increase the solid angle, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8][9][10][11][12][13] In recent years, new high resolution soft X-ray spectrometers based on varied line spacing gratings have been build. [20][21][22][23][24][25] Some are even able to resolve vibrational states in the spectrum. 26 Yet, they are huge setups with detector arm length of up to 5 m. 22 Future spectrometer projects are even planned with detector arm length up to 15 m with the aim to reach higher resolving power.…”
Section: Introductionmentioning
confidence: 99%